Coupled Coil Design and Magnetic Field Characteristics Analysis of Wireless Power Transfer System Based on Semi-closed Domain Coupling Resonance - ZHOU Xiwei; YANG Zewang; BAI Yehong; SHANG Xinjuan (Kongzhi Yu Xinxi Jishu)
Wireless power transfer technology based on magnetic coupling resonance is a frontier subject in the field of power transfer and has great application prospects. In order to improve the performance of wireless power transmission system, it is necessary to optimize the design of magnetic coupling resonant coil. In this paper, under the semi-closed nonlinear coupling state with radial, angular and radial-angle offsets, a 3D model of coupling coil is established for wireless power transmission system, and a new genetic algorithm is used to determine the parameters of the coupling coil. Through electro-magnetic joint simulation of the resonant circuit model, field strength distribution and transfer characteristics of the system under the design parameters are obtained, which verifies the validity of the parameters and provides an effective method for the design of magnetic coupling resonant coil.